2021
DOI: 10.1002/agj2.20919
|View full text |Cite
|
Sign up to set email alerts
|

The role of precision agriculture in food security

Abstract: Precision agriculture (PA) is the application of information technology to better manage crop and livestock production, heralded as another tool to advance food security around the world. Precision agriculture has the potential to increase productivity, improve resource allocation for inputs such as pesticides, fertilizers, water, feed, and labor, provide for more stable production, and reduce agricultural production's environmental effect. But PA is an approach that can be very different depending on farm cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Experts on the panel were in 90 to 100% consensus on three hot topic issues: soil health and water usage, climate and environmental factors, and research and collaboration (more data on the topics, interdisciplinary collaboration, and sharing of information within research groups as well as with farmers). In addition, workforce training (see Erickson & Fausti, 2021), accessibility of germplasm (see Smith et al., 2021), chemical usage, (including weed resistance (see Clay, 2021 and disease problems discussed in Byamukama et al., 2021), and economic stability and governmental policy focused on the agricultural sector (discussed in Joshi et al., 2021, and Barrera et al., 2021) were recognized as urgent topics that must be addressed to continue to have sustainable production agriculture in the future.…”
Section: Critical Issues Facing Food Production and The Ag Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Experts on the panel were in 90 to 100% consensus on three hot topic issues: soil health and water usage, climate and environmental factors, and research and collaboration (more data on the topics, interdisciplinary collaboration, and sharing of information within research groups as well as with farmers). In addition, workforce training (see Erickson & Fausti, 2021), accessibility of germplasm (see Smith et al., 2021), chemical usage, (including weed resistance (see Clay, 2021 and disease problems discussed in Byamukama et al., 2021), and economic stability and governmental policy focused on the agricultural sector (discussed in Joshi et al., 2021, and Barrera et al., 2021) were recognized as urgent topics that must be addressed to continue to have sustainable production agriculture in the future.…”
Section: Critical Issues Facing Food Production and The Ag Workforcementioning
confidence: 99%
“…As technology becomes more common place in crop production, a well-trained workforce is imperative to empower the best use of the technology (Erickson & Fausti, 2021). This means that users will need training in crop production best management practices, as well as when, where, and what technology is appropriate to be deployed in specific circumstances.…”
Section: Critical Issues Facing Food Production and The Ag Workforcementioning
confidence: 99%
“…In addition, socio-economic barriers do matter, such as openness to innovation, knowledge sharing, age, complexity and cost of technology, available financial support, and farm size (Blasch et al, 2022). These are among the reasons why PA adoption shows different characteristics compared to other agricultural innovations, such as a slower adoption process for some technologies and greater divergence between the different farms (Erickson and Fausti, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Lowenberg-DeBoer and Erickson (2019) identified that non-mechanized, small and medium-sized farms in developing countries have the lowest PA adoption. It should be highlighted that most of the African and Asian small-scale farms are generally non-mechanized; therefore, nondigital-based PA technologies are particularly important for them (Erickson and Fausti, 2021). Although this problem of mechanization and/or adoption is more significant in developing countries, some of the smallholdings in developed countries can also be concerned.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the use of technologies in agriculture has also increased significantly through the usage of geographic information systems (GIS), and global navigation satellite systems (GNSS), remote sensing, RPAS, machinery and other technologies that have supported precision agriculture [5][6][7]. The incorporation of these disciplines allows the collection, processing and analysis of temporal, spatial and individual data and combines them with other data for the implementation of adequate solutions in the use of resources, productivity, quality, profitability and sustainability of agricultural production [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%